Irreversible capacity losses upon lithium insertion/extraction in graphite – silicon electrodes - Kuksenko, S. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
Сomposites were prepared by mechanical milling containing graphite and fine silicon particles. The microstructure, morphology, nature of the surface compounds, and electrochemical performance of these materials were analyzed by SEM, XPS, and electrochemical methods. Hybride electrode on the base of mixture of artificial graphite MAG D-20 and silicon ballmilled in the presence of graphite have shown on irreversible loss of capacity as a result of reductive reactions in the natural surface layer of silicon oxide involving silanol groups; it has given as a possibility to increase reversible specific capacity up to 445 mAh/g with the first cycle efficiency of 92.6 %.